Sarcoma Subgrouping by Detection of Fusion Transcripts Using NanoString nCounter Technology. (May 2019) - Sheth, Javal; Arnoldo, Anthony; Zhong, Yunan; Marrano, Paula; Pereira, Carlos; Ryall, Scott; Thorner, Paul; Hawkins, Cynthia; Somers, Gino R
Background: NanoString technology is an innovative barcode-based system that requires less tissue than traditional techniques and can test for multiple fusion transcripts in a single reaction. The objective of this study was to determine the utility of NanoString technology in the detection of sarcoma-specific fusion transcripts in pediatric sarcomas. Design: Probe pairs for the most common pediatric sarcoma fusion transcripts were designed for the assay. The NanoString assay was used to test 22 specific fusion transcripts in 45 sarcoma samples that had exhibited one of these fusion genes previously by reverse transcription polymerase chain reaction (RT-PCR). A mixture of frozen (n = 18), formalin-fixed, paraffin-embedded (FFPE) tissue (n = 23), and rapid extract template (n = 4) were used for testing. Results: Each of the 22 transcripts tested was detected in at least one of the 45 tumor samples. The results of the NanoString assay were 100% concordant with the previous RT-PCR results for the tumor samples, and the technique was successful using both FFPE and rapid extract method. Conclusion: Multiplexed interrogation for sarcoma-specific fusion transcripts using NanoString technology is a reliable approach for molecular diagnosis of pediatric sarcomas and works well with FFPE tissues. Future work will involve validating additional sarcoma fusion transcripts as well as determining the optimal workflow for diagnostic purposes.